Associations between seasonal variation and post-operative complications after total hip arthroplasty - Ng, Mitchell (Ann Transl Med, 2017)
BACKGROUND: Total hip arthroplasty (THA) complication rates are low, but pose marked challenges during the post-operative care period. Therefore, it is important to determine which risk factors are associated with an increased rate of these complications. The purpose of this paper was to investigate the association between seasonal variations and the 30-day post-operative complication rates following THA. Specifically, we evaluated a large prospectively collected national database for: (I) overall complication rates; (II) seasonal variations in incidence; and (III) specific quarter (Q), if any, associations. METHODS: This multi-center observational cohort study was conducted by analyzing 102,682 THA surgeries listed in the American College of Surgeon National Surgical Quality Improvement Program database (ACS-NSQIP) from January 1st, 2011 to December 31st, 2015. All surgeries were divided into four groups based on the quarter of the year in which the surgery was performed. We identified 20 complications listed in the ACS-NSQIP and calculated 30-day post-operative complication rates. Univariate analysis was performed to compare complication rates between different seasons. Multivariate analysis was performed to control for potential confounding variables. RESULTS: The overall complication rate in this cohort was 1.09%. Upon tabulation of the different post-operative THA complication incidence rates sorted by quarters, 16 out of 20 outcomes had <1% incidence rate, 3 had between a 1% and 5% incidence rate, and 1 outcome had a complication rate greater than 5% (bleeding transfusion). There were no statistical differences in 19 of the 20 complication rates when compared between the different quarters. Transfusion was the only complication with a statistically significant difference (P value <0.001) between the different quarters, which demonstrated a marked increase in Q3/Q4 (July to December), when compared to Q1 (January to March) (P<0.001). CONCLUSIONS: Overall, our results indicate a low complication rate in this cohort of patients who underwent a THA (1.09%). There was no correlation between seasonal variation and 30-day complication rates following THA, except for bleeding risk, which remains unexplained. These findings suggest that elective THA does not have to be scheduled around specific times of the year in order to avoid 30-day post-operative complications.